한국형 (韓國型) 출혈열 (出血熱) - 이호왕; 李鎬汪; 이평우; 이평우; 백락주; 白樂柱; 김대식; 金大植; 김원동; 金源東; 조보?; 趙普?; et al. (Journal of bacteriology and virology, 1980)
Epidemic hemorrhagic fever was recognized for the first in Korea in 1951 during Korean War among United Nations troops although similar diseases to Korean hemorrhagic fever(KHF) have been described by Japanese in China and by Russian in the Soviet Union. Since that time it has been known as Korean hemorrhagic fever and has remained endemic near the Demilitarized Zone between North and South Korea. In recent years, the disease has invaded the southern parts of the Korean peninsula and 100 to 800 hospitalized cases are clinically diagnosed each year. In 1976 Lee and Lee successfully demonstrated an antigen in the lungs of Apodemus agrarius coreae which gave specific immunofluorescent reaction with sera from patients of KHF and named it as Korea antigen. Very recently, Lee et al have reported that this antigen is the etiologic agent of KHF for the first time, and convalescent sera from hemorrhagic nephroso-nephritis in the Soveit Union, from nephropathia epidemica in Scandinavia and from epidemic hemorrhagic fever in Japan were positive for antibodies to Hantaan virus and have perfected serologic test for diagnosis of the disease. This report describes on serologic diagnosis of KHF patients and persistence of immunofluorescent antibodies to Hantaan virus after recovery of illness. 1. Immunofluorescent antibodies against Hantaan virus were appeared right after onset of fever. The highest titers were observed at 2 to 3 weeks followed by a slow decline. Antibodies also were present in each of 13 sera obtained from patients with KHF 3 to 14 years after acute disease. 2. It was possible to diagnose KHF serologically since all of the KHF patient produced antibodies against Hantaan virus by 10 days after onset of illness. 3. Occurrence of antibodies to Hantaan virus in normal Korean was 2.6% and all of the positive sera were from adults. 4. Accuracy of clinical diagnosis of KHF in suspected cases of KHF patieats at hospitals in Seoul was about 50% in compare with serologic diagnosis of the disease.